Live Respiratory Syncytial Virus Attenuated by M2-2 Deletion and Stabilized Temperature Sensitivity Mutation 1030s Is a Promising Vaccine Candidate in Children. (23rd November 2019) - McFarland, Elizabeth J; Karron, Ruth A; Muresan, Petronella; Cunningham, Coleen K; Libous, Jennifer; Perlowski, Charlotte; Thumar, Bhagvanji; Gnanashanmugam, Devasena; Moye, Jack; Schappell, Elizabeth; Barr, Emily; Rexroad, Vivian; et al.
Abstract: Background: The safety and immunogenicity of live respiratory syncytial virus (RSV) candidate vaccine, LID/ΔM2-2/1030s, with deletion of RSV ribonucleic acid synthesis regulatory protein M2-2 and genetically stabilized temperature-sensitivity mutation 1030s in the RSV polymerase protein was evaluated in RSV-seronegative children. Methods: Respiratory syncytial virus-seronegative children ages 6–24 months received 1 intranasal dose of 10 5 plaque-forming units (PFU) of LID/ΔM2-2/1030s (n = 21) or placebo (n = 11). The RSV serum antibodies, vaccine shedding, and reactogenicity were assessed. During the following RSV season, medically attended acute respiratory illness (MAARI) and pre- and postsurveillance serum antibody titers were monitored. Results: Eighty-five percent of vaccinees shed LID/ΔM2-2/1030s vaccine (median peak nasal wash titers: 3.1 log10 PFU/mL by immunoplaque assay; 5.1 log10 copies/mL by reverse-transcription quantitative polymerase chain reaction) and had ≥4-fold rise in serum-neutralizing antibodies. Respiratory symptoms and fever were common (60% vaccinees and 27% placebo recipients). One vaccinee had grade 2 wheezing with rhinovirus but without concurrent LID/ΔM2-2/1030s shedding. Five of 19 vaccinees had ≥4-fold increases in antibody titers postsurveillance without RSV-MAARI, indicating anamnestic responses without significant illness after infection with community-acquired RSV. Conclusions: LID/ΔM2-2/1030s had excellent infectivity without evidence of genetic instability, induced durable immunity, and primed for anamnestic antibody responses, making it an attractive candidate for further evaluation. Abstract : Live respiratory syncytial virus (RSV) vaccine LID/∆M2-2/1030s attenuated by deletion of the RNA regulatory protein M2-2 and temperature-sensitivity mutation 1030s had excellent immunogenicity and genetic stability in RSV-seronegative 6- to 24-month-old children, making it an attractive candidate for further evaluation.